New sensitive method for HEPES quantification in 68Ga-radiopharmaceuticals - I. F. Antunes; G. M. Franssen; R. Zijlma; P. Laverman; H. H. Boersma; P. H. Elsinga (EJNMMI Radiopharmacy and Chemistry, 2020)
Abstract Background The introduction of a GMP-certified 68Ga-generator spurred the application of 68Ga-radiopharmaceuticals. Several radiosynthesis of 68Ga-radiopharmaceuticals are more efficient and robust when performed with 2-[4-(2-hydroxyethyl)piperazin-1-yl] ethanesulfonic acid (HEPES) buffer, which is considered as an impurity in the quality control (QC) procedure. Thus, prior to clinical use, QC must be conducted to ensure that HEPES does not exceed the maximum dose of 200 μg/V Injected as described in European Pharmacopoeia (Ph Eur) for edotreotide. However, when applying the thin-layer chromatography (TLC) method described in the Ph Eur to quantify the HEPES amount present in the 68Ga-octreotide or in the remaining 68Ga-radiopharmaceuticals that were tested, no amount was detectable after 4 min of iodine incubation. Here we tested our modified TLC method and validate a new high-performance liquid chromatography (HPLC) method to quantify HEPES in 68Ga-radiopharmaceuticals and compare it to the TLC-method described in Ph Eur. In addition, samples collected from various institutes were tested to evaluate whether the synthesis of different 68Ga-radiopharmaceuticals or the use of different synthesis methods could affect the amounts of HEPES. Results HEPES could not be detected by the TLC method described in the Ph Eur within 4 min incubation in an iodine-saturated chamber. As for our modified TLC method, only after 2 h, spots were only visible > 1 mg/mL. The HPLC method had a limit-of-quantification (LOQ) of 3 μg/mL and a limit-of-detection (LOD) of 1 μg/mL. From the three 68Ga-radiopharmaceuticals tested, only in the [68Ga]Ga-NODAGA-Exendin samples exceeding amounts of HEPES were found and its concentration in the [68Ga]Ga-NODAGA-Exendin was significantly higher, when compared to [68Ga]Ga-DOTATOC and [68Ga]Ga-PSMA-11. Conclusion The TLC method described in Ph Eur and our modified TLC method may not be sufficiently sensitive and thus unsuitable to use for QC release. The new HPLC method was sensitive, quantitative, reproducible and suitable for QC release. With this method, we were able to determine that some 68Ga-radiopharmaceuticals may exceed the HEPES limit of 200 μg/ V Injected. This new analytical system would allow correcting for the maximum injected dose in order not to exceed this amount.